The singing - Multidimensional analysis of immaterial culture. Validation of the Portuguese Singing Voice Handicap Index (SVHI) version and Agustin Escolano Benito's Hermeneutic / Interpretive Model Hermenêutico/interpretativo de Agustin Escolano Benito (Cadernos de Sociomuseologia, 2017)
This article aims to present a point of reflection, the trajectory of knowledge and concepts, apparently as different as medicine and culture. The multidimensional analysis of singing and the validation of the version of the Singing Voice Handicap Index (SVHI), translated and adapted culturally to the Portuguese language of Portugal, reminds us, in its assumptions, the Agustin Escolano Benito´s interpretative model of culture. The questionnaire used in the evaluation of disadvantage insingers with vocal problems (SVHI), in which data of different natures are present for analysis, presupposes, rather than the physiological body, the cultural body in which scientific culture is manifested and interacted, political culture And empirical culture. It is this body, as heritage to be preserved, that is read as narrative with the details of its uniqueness. The article presents the interpretive model of culture and advances to the concept of voice, to focus on the study of multidimensional analysis of voice, adding the model to the list of translated versions (now for Portuguese). Finally, it is demonstrated that the Portuguese version of the SVHI is a reliable and valid instrument in the evaluation of the vocal disadvantage in the Portuguese singers and can be added to the list of translated versions of this instrument originally created for the vocal evaluation of the Englishspeaking singers of America., and that the model of analysis of Escolano Benito is valid for other cultural universes that not only the school culture.Key words: Cultural body, Culture, Intangible Culture, Voice, Hermeneutic/interpretive model of Agustin Escolano Benito, Invalidity assessment; Vocal disorders, Multidimensional Voice Analysis (SVHI) index (questionnaire) of the vocal disadvantage in the corner.